Improved solvent economy and rate of rice bran lipid extraction using hydrolyzed rice bran with hexane as solvent. (November 2020) - Go, Alchris Woo; Pham, Thi Yen Nhu; Truong, Chi Thanh; Quijote, Kristelle L.; Angkawijaya, Artik Elisa; Agapay, Ramelito C.; Gunarto, Chintya; Ju, Yi-Hsu; Santoso, Shella Permatasari
Abstract: This study provides kinetic and equilibrium information of the extraction of rice bran lipids using hexane from post-hydrolysis rice bran (PHRB). Rice bran (RB) is an agricultural residue with promising valorization potential in biodiesel production. In this study, native RB was subjected to dilute acid hydrolysis (DAH) with an acid solution 3 vol% using 95 wt% H2 SO4 at 90 °C for 6 h, increasing the lipid density threefold. Batch extraction with hexane was carried out at various temperatures (30, 45, and 60 °C) and solvent to solid ratio (SSR, 4, 8, and 12 mL g −1 ). Improved extraction rates were observed at higher temperatures and lower SSRs. Regardless, ~90% of the extractable lipids were solubilized in hexane in less than 10 min. Data obtained were fitted with 5 different models. The extraction of lipids from RB and PHRB involves at least 2 mechanisms, a rapid washing step, and a diffusion step. The extraction process was found to be exergonic, endothermic, and irreversible. An SSR of 4 mL g −1 would require at least 5 ideal crossflow extraction stages for a lipid recovery of over 95%. Compared to RB, the extraction of lipids from PHRB provides potential solvent savings of ~80%. Highlights: The highlights of this manuscript: Post-hydrolysis rice bran (PHRB) contain more lipids than native RB. Lipids recovered from PHRB are suitable as feedstock for biodiesel production. At least 90% of the available lipids could be extracted in 5 min. Up to 80% less solvent is required to recover the same amount of lipids from PHRB.